ANALYSIS OF FM BROADCAST RADIO SIGNAL RECEPTION IN BORDER AREAS USING SEVERAL ANTENNA MODELS - Al Muflihin, Amru Hisyam; Imansyah, Fitri; Kusumawardhani, Eka (Faculty of Engineering, Universitas Tanjungpura, 2023)
Information is now a basic need for every people, including the people in border areas. Therefore, it is an obligation for the government to provide information media that can be reached by all levels of society, one of which is FM radio broadcast media. This research aims to identify and assess the quality of FM radio broadcasts in the border area of Sambas Regency using several antenna models which in the area is a vulnerable area of signal leakage by neighbouring countries and far from Indonesian broadcast transmitters. The assessment of FM radio broadcast quality is carried out with the determination of SINPO (Signal, Interference, Noise, Propagation, Overall) values and field strength meter measurements. The data obtained were analysed using the Miles and Hubberman interactive data processing technique. From the research conducted, it was found that 10 Malaysian FM radio broadcast channels and 2 broadcast channels from Indonesia where the dominant broadcast was received better by the yagi antenna. There were also broadcasts whose frequencies fell out of compliance with the regulations.